Integrasi Islam dan Budaya: Studi Budaya Bakar Batu Masyarakat Papua Pegunungan di Kota Jayapura - Dute, Hasruddin (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2022)
This study aims to determine the process of stone-burning culture for the Papuan Muslim Mountain community in the city of Jayapura where the process is carried out by making pigs as game animals to be burned in stone-burning culture. This research is a qualitative descriptive study, which tries to describe objectively and accurately about the tradition of burning stones in the Muslim highlands of Papua. Conducting interviews with informants who have lived in high-rise areas in the city of Jayapura. The results of this study indicate that the culture of burning stones in the Muslim Papuan community is carried out as a form of gratitude for the gift from God for this gift. Burning stones is done by stacking chicken and meat as the main dishes on a stone that has been burned first, then sweet potatoes, cassava, and vegetables in the next section. At the last or the very top will be given a stone that has been burned. In the implementation of this stone burning is carried out by the people of Papua in the central mountains who are Muslim, especially those who live in the city of Jayapura. This activity has been carried out since the second generation of mountainous Papua converted to Islam where the meat that is burned is chicken as a substitute for pork which is an animal that will be burned in stone-burning cultural activities. Islam has brought about a change in the Papuan Muslim Mountain community living in Jayapura. However, the residents until now still maintain their ancestral customs. Traditions that are still valid and preserved in the Bakar Batu tradition.